Understanding Pasefika perceptions and experiences of the school system in Years 7 to 10 : a thesis presented in partial fulfilment of the requirements for the degree of Master of Education at Massey University, Palmerston North, New Zealand - Malaulau, Dinah (Massey University, 2009)
Drawing on questionnaires and interviews of Pasefika students, their parents, and teachers, this case study provides an understanding of their perceptions and experiences of the school system in Years 7 to 10 within a family resource framework. Essentially, the financial, social and cultural resources available to Pasefika students within the context of their family's cultural capital, and their prior cognitive ability and non-cognitive dispositions have greater influence on their engagement and success at school than their culture or ethnicity. Respondents' suggestions for changes to enhance schooling and the social and educational needs of Pasefika students, including the support for a middle-school structure and provision of an extra year prior to NCEA qualifications, reiterate similar multivariate recommendations and findings of other studies.
Keywords: New Zealand; Pacific Islanders -- Education (Secondary); Home and school